KERAGAAN UBI JALAR [IPOMOEA BATATAS (L) LAM.] AKIBAT PEMBERIAN BIOCHAR JENGKOK TEMBAKAU - Lein, Johanes; Indawan, Edyson; Sumiati, Astri (Universitas Tribhuwana Tunggadewi, 2019)
Sweet potatoes including tuber commodities that have important prospects. Due to the high content of nutrients, minerals, vitamins and the increasing diversity of processed and industrial products sourced from sweet potatoes. The improvement of sweet potato production is still being carried out, one of the improvements in soil improvement. Provision of biochar into the soil can increase the availability of the main ratio, P and N concentrations in the soil. Increased CEC and soil pH can increase 40% Biochar's ability to bind water and nutrients in the soil helps prevent fertilizer losses due to surface erosion and washing so as to enable fertilizer savings. This study aims at agronomic performance in sweet potato plants due to biochar administration. The experiment was carried out using splitplots with 3 replications, 7 varieties namely: white brass, red brass, Beta 1, Beta 2, Sari, Boko, Jago and Biochar Dose: (Bo = No Biochar, B1 = 5 tons / ha). Variables observed included: number of tubers / plot, tuber fresh weight (kg / plot), freshly squeezed weight (kg / plot),% tuber dry weight (BK) tubers,% tuberous dry weight, tuber BK weight, and stover BK. Continued testing with the smallest Real Difference Test (LSD) with a confidence level of 5% based on research shows that the performance of yarbaik varieties in tubers is Beta 1 with the number of tubers / plots of 39.67 tubers, Beta 2 at tuber weights of 8.60 kg / plant , Beta 1 10.92 kg / fresh weight crop of stover, Sari and Beta 2 at harvest index are 92.25 and 88.81 tubers. Ubi jalar termasuk komoditas umbi-umbian yang mempunyai prospek penting. Karena tingginya kandunggan nutrisi, mineral, vitamin dan semakin beragamannya produk olahan maupun industri yang bersumber dari ubi jalar. Peningkata produksi ubi jalar masih terus dilakukan, salah satu perbaikan pembenahan tanah. Pemberian biochar ke dalam tanah dapat meningkatkan ketersediaan katioan utama, P dan konsentrasi N dalam tanah. Peningkatan KTK dan pH tanah dapat meningkat 40% Kemampuan biochar untuk mengikat air dan unsur hara dalam tanah membantu mencegah terjadinya kehilangan pupuk akibat erosi permukaan dan pencucian sehingga dapat memungkinkan penghematan pemupukan. Penelitian ini bertujuan keragaan agronomi pada tanamanubi jalar akibat pemberian biochar. Percoban di laksanakan dengan menggunakan splitplot denang 3 ulangan, 7 varietas yaitu: Kuningan putih, kuningan merah, Beta 1, Beta 2, Sari, Boko, Jago dan Dosis Biochar : (Bo= Tanpa Biochar, B1=5 ton/ha). Variabel yang di amati meiputi: jumlah umbi/plot, bobot segar umbi (kg/plot), bobot segar berangkasan (kg/plot), % bobot kering (BK) umbi, % bobot kering berangkasan, BK umbi, dan BK brangkasan. Pengujian lanjutan denagn Ujian Beda Nyata terkecil (BNT) dengan taraf kepercayaan 5% berdasarkan penelitian menunjukkan bahwa keragaan Varietas yarbaik pada umbi yaitu Beta 1 dengan jumlah umbi/plot sebanyak 39,67 umbi, Beta 2 pada bobot umbi sebesar 8,60 kg/tanaman, Beta 1 10,92 kg/pertanaman berat segar brangkasan, Sari dan Beta 2 pada indeks panen yaitu 92,25 dan 88,81 umbi.